Let them eat shrimp the tragic disappearance of the rainforests of the sea - Warne, K. P. (Island Press, 2011)
What's the connection between a platter of jumbo shrimp at your local restaurant and murdered fishermen in Honduras, impoverished women in Ecuador, and disastrous hurricanes along America's Gulf coast? Mangroves. Many people have never heard of these salt-water forests, but for those who depend on their riches, mangroves are indispensable. They are natural storm barriers, home to innumerable exotic creatures from crabeating vipers to man-eating tigers and provide food and livelihoods to millions of coastal dwellers. Now they are being destroyed to make way for shrimp farming and other coastal development. For those who stand in the way of these industries, the consequences can be deadly. In Let Them Eat Shrimp, Kennedy Warne takes readers into the muddy battle zone that is the mangrove forest. A tangle of snaking roots and twisted trunks, mangroves are often dismissed as foul wastelands. In fact, they are supermarkets of the sea, providing shellfish, crabs, honey, timber, and charcoal to coastal communities from Florida to South America to New Zealand. Generations have built their lives around mangroves and consider these swamps sacred. To shrimp farmers and land developers, mangroves simply represent a good investment. The tidal land on which they stand often has no title, so with a nod and wink from a compliant official, it can be turned from a public resource to a private possession. The forests are bulldozed, their traditional users dispossessed. The true price of shrimp farming and other coastal development has gone largely unheralded in the U.S. media. A longtime journalist, Warne now captures the insatiability of these industries and the magic of the mangroves. His vivid account will make every reader pause before ordering the shrimp.